The Metal Art Industry in Tumang, Cepogo, Boyolali: Preservation and Development Recommendation Policy - Widhyasmaramurti Widhyasmaramurti; Ari Prasetiyo; Dwi Kristianto (Indonesian Journal of Multidisciplinary Science, 2022)
Nowadays, the craftsman is considered a profession that does not need higher education requirements; thus, it creates a wider gap in the craftsmen's regeneration. Tumang's younger generation prefers to work as resellers instead of becoming craftsmen. This study aims to provide policy recommendations that support the preservation of the Tumang Copper Craft Art as traditional Indonesian knowledge. The research uses a qualitative method with a participatory action research approach. It focuses on group discussions with copper artisans and sellers in Tumang on collecting data on the field's challenges and interviews with policymakers to obtain appropriate policy recommendations. The results show that supporting the regeneration process is necessary. The request of public policy needs to be linked to formal education in schools through the Education and Culture Office and efforts to increase the capacity of artisans through the Community and Village Empowerment Service. Moreover, to ensure that the recommendation to support the preservation and development of the Copper Craft Art can be implemented, a public policy recommendation with legality is in the form of a Regent's Regulation because it may cover both education and community empowerment in Tumang.